2010
DOI: 10.3122/jabfm.2010.05.100024
|View full text |Cite
|
Sign up to set email alerts
|

What Words Should We Use When Discussing Excess Weight?

Abstract: Background: There is limited research on how patients prefer physicians to communicate about the topic of obesity, and there is even less understanding of which terms physicians most commonly use.Methods: In this cross-sectional, nonrandom sampling study, patients who were seeking treatment for weight loss rated the desirability of 12 terms to describe excess weight, and physicians rated the likelihood with which they would use those terms during clinical encounters. Participants rated terms on a 5-point scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 20 publications
11
74
0
4
Order By: Relevance
“…These findings were similar to preferences documented among treatment-seeking adults with overweight and obesity. 32,33 Our findings remained consistent across sociodemographic variables, including gender, race, income, education, and parent and child's body weight. The age effects observed indicate the need for additional research to clarify whether preferences of weight-based language shift as parents (and their children) become older.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These findings were similar to preferences documented among treatment-seeking adults with overweight and obesity. 32,33 Our findings remained consistent across sociodemographic variables, including gender, race, income, education, and parent and child's body weight. The age effects observed indicate the need for additional research to clarify whether preferences of weight-based language shift as parents (and their children) become older.…”
Section: Discussionsupporting
confidence: 65%
“…Two studies of adults seeking treatment for overweight and obesity revealed that "obese" and "fat" were rated as undesirable terms, and "weight" and "BMI" were preferred. 32,33 Others studies have revealed that "obese" may be perceived as a negative term, 34,35 perhaps because of implications of more serious medical consequences and a sense of confusion it may invoke. 30 Among parents, in 1 qualitative study parents were found to prefer that physicians call their children "overweight" and "obese" instead of more colloquial terms (eg, "chubby" or "plump"), 36 and another reported study "obese" and "fat" were found to be parents' least preferred terms.…”
mentioning
confidence: 99%
“…La EM es un enfoque centrado en el paciente y la familia, que pretende la toma de decisiones de forma colaborativa, proporciona feed-back sin enjuiciar, acepta la resistencia al cambio por parte del paciente y les anima a desarrollar sus propios motivos para el cambio de conducta de salud 9,10 .…”
Section: Fundamentos De La Entrevista Motivacionalunclassified
“…Esto no quiere decir escuchar en silencio reflexionando o haciendo hipótesis para uno mismo, sino que tras cada respuesta del paciente se le devuelve una reflexión o un resumen, para comprobar si es eso lo que quiere decir 9,11,12 . Buscando el significado detrás de las palabras del paciente.…”
Section: Escucha Reflexivaunclassified
“…Obesity and diabetes prevention and intervention can occur at key opportunities, such as in the primary care office during a routine office visit or an annual physical [53]. The PCP has the unique advantage of seeing patients for various health concerns, creating many opportunities to address their weight issues [11].…”
Section: Pcp and Interventionmentioning
confidence: 99%